Vegetative valvular endocarditis in a calf: a clinical report - Adamu, Lawan; Abdullah, Faez Firdaus Jesse; Osman, Abdinasir Yusuf; Sabri, Jasni; Norsidin, Mohd Jefri; Saad, Mohammad Zamri; Haron, Abdul Wahid; Saharee, Abdul Aziz (KPK Publishers, 2014)
A one month old male Brangus calf with a history of navel ill was referred to the veterinary hospital at University Putra-Malaysia. The calf was pyrexic, dull and depressed with increased respiratory and heart rates. The calf did not respond to the treatment and died. Grossly, the carcass was emaciated and pale. Post-mortem examination revealed oedematous lungs with frothy tracheal exudates, congested kidneys and cauliflower like lesions on both valves of the heart. Histopathologically, necrosis and haemorrhage were observed in the cardiac valves with infiltrations of bacterial colonies. Degeneration and necrosis of many renal tubular cells with evidence of detachment of these cells into the tubular lumen and septic emboli were also seen. In the brain, there were neuronal degeneration, necrosis and vascular injection of small vessels. All findings confirmed the diagnosis of septicemic and vegetative valvular endocarditis squeal to navel ill caused by E. coli infection.